A Research in Muhammadiyah University of Enrekang: The Human Reseources Management and Human Capital in Educational Institution - Sudirman Sudirman; Akbar Akbar; Sulaiman Sulaiman; Elihami Elihami; Abdullah Abdullah (EduPsyCouns: Journal of Education, Psychology and Counseling, 2020)
This research discussed about the teaching of languages to speak Indonesian well and correctly through speaking aspects and language elements in various contexts. This research focused the researcher was intrigued to carry out an experiment on the learning-teaching strategy of pragmatics and to know the students’ achievement level in Indonesian who were taught by using pragmatics and those who were taught without using pragmatics, particularly the first semester students of Muhammadiyah University of Enrekang. The research was an experimental research whose samples consisted of 55 students taken by using random sampling out of the population whose number was 578 students. The scientific fact found in this research showed that the learning-teaching strategy of pragmatics is one of the approaches that can be taken into consideration to be developed and socialized to Muhammadiyah University of Enrekang lectures. The results of the research showed that there is a difference in the students’ learning achievement in Indonesian between those who were taught by using pragmatics and those who were taught without using pragmatics. The data for the students’ learning achievement in Indonesian were collected by using the instrument in the form of a test carried out before and after the treatment. Those data were analyzed by using descriptive and inferential statistic analysis. Most of the functions used of the originality of this study of the learning-teaching processes of Indonesian in general and the students’ learning achievement in Indonesian in particular can be maintained and promoted in the effort of making the students fluent and familiar with the use of Enrekang daily.